The Quality Of Finishes On Plantation Grown Timber Species - Karmin (1990)
Tests to determine the quality of finish of nitrocellulose and acid catalysed lacquer with and without sanding between coatings were conducted on four fast growing species , namely : batai , yamane , acacia , and rubberwood. The quality of finishes was evaluated in terms of machining ability , surface performace , surface gloss , adhesion ability , hardness , and flexibility of wood finish . The testing methods were based on The British Standard No . 3962 part 6 , 1980 and Draft of Malaysian Standard part 1 ,1987 . The results indicated that on rubberwood , acacia, batai and yamane nitrocellulose lacquer had higher gloss and was more flexible than acid catalysed lacquer with and without sanding in between coatings.On the other hand , acid catalysed lacquer had greater hardness and higher adhesion ability than nitrocellulose lacquer with and without sanding in between coatings for all species. In general the quality of nitrocellulose lacquer and acid catalysed lacquer on rubberwood was the highest , followed by acacia, yamane , and batai . Moreover , these species have a good machining ability and have a good surface performance , and the results showed rubberwood , acacia and yamane to be suitable for furniture.